Aleurites moluccana (L.) Willd. Leaves: Mechanical Antinociceptive Properties of a Standardized Dried Extract and Its Chemical Markers. (26th April 2011) - Quintão, Nara L. M.; Meyre-Silva, Christiane; Silva, Gislaine F.; Antonialli, Carla S.; Rocha, Lilian W.; Lucinda-Silva, Ruth M.; Malheiros, Angela; Souza, Márcia M.; Cechinel Filho, Valdir; Bresolin, Tania M. B.
Abstract : Seeking to develop a new analgesic phytomedicine, a spray-dried extract (SDE) of Aleurites moluccana (L.) Willd. leaves was developed in scale up (5 kg). The SDE was standardized at 3% w/w in relation to the flavonoid 2 ′′ - O -rhamnosylswertisin. The SDE batches were evaluated in relation to their physical, physiochemical, and pharmacological characteristics. The results demonstrated the reproducibility of the scale up SDE process which, when dosed orally, reduced carrageenan-induced mechanical hypernociception, with an ID50 % of 443 mg/kg. Similar results were obtained with animals injected with complete Freund's adjuvant (CFA), in which SDE caused inhibition of 48 ± 4%. SDE was effective in preventing prostaglandin E2 (PGE2)-induced mechanical hypernociception (inhibition of 26 ± 10% and 33 ± 3%, at 250 and 500 mg/kg, respectively). Swertisin and 2 ′′ - O -rhamnosylswertisin isolated from the own extract were effective in inhibiting the hypernociceptive response induced by carrageenan (70 ± 2% and 50 ± 5%, resp.). Furthermore, 2 ′′ - O -rhamnosylswertisin was capable of significantly inhibiting the mechanical sensitization induced by CFA or PGE2, with inhibitions of 25 ± 3% and 94 ± 6%, respectively. These results suggest that the effects of SDE are related, at least in part, to the presence of these flavonoids.